Osthole/borneol thermosensitive gel via intranasal administration enhances intracerebral bioavailability to improve cognitive impairment in APP/PS1 transgenic mice - Wu, Fanchang; Huang, Mingjun; Zuo, Xue; Xie, Ruiye; Liu, Jinman; Ke, Junyu; Li, Weirong; Wang, Qi; Liang, Yong (Frontiers in Pharmacology, 2023)
Alzheimer’s disease (AD) poses a significant threat to the global elderly population. Traditional Chinese Medicine (TCM) has been widely utilized in the treatment of AD. Osthole, a bioactive ingredient classified as an “Emperor” in many TCM formulas, has been demonstrated to effectively alleviate AD symptoms. However, its low bioavailability in the brain has limited its clinical application. This study aimed to increase the intracerebral bioavailability of osthole through the use of borneol as a “Courier,” based on the classical “Emperor-Minister-Assistant-Courier” theory, and to investigate the enhanced pharmacological performance of osthole towards AD. Results indicated that a suitable in-situ thermosensitive gel matrix for intranasal administration mixed with osthole and borneol consisted of P407 at 20%, P188 at 7%, and PEG300 at 6%. The concentration of osthole in cerebrospinal fluid increased almost tenfold after intranasal administration of osthole/borneol compared to oral administration. Mechanisms showed that borneol as a “Courier” opened up intercellular space and loosened tight junctions of nasal mucosa by suppressing ZO-1 and Occludin expression, thereby expediting the nose-to-brain route and guiding osthole as an “Emperor” to its target in the brain. Osthole assisted by borneol demonstrated significantly improved efficiency in suppressing cleaved Caspase-3 expression, increasing the Bcl-2/Bax ratio, improving T-SOD and catalase expression, reducing Malondialdehyde levels, inhibiting neuron apoptosis, and decreasing Aβ levels by inhibiting BACE1 expression to improve cognitive impairment in APP/PS1 mice compared to osthole alone. Overall, our study demonstrated that intracerebral bioavailability of osthole was profoundly improved with intranasal administration of osthole/borneol and provided wider application of TCM for AD treatment with higher intracerebral bioavailability.